The Effectiveness of Communicative Language Teaching towards Students’ Ability in Essay Writing - Nurhayati Sitorus; Nenni Triana Sinaga; Romaulu Siahaan; Nanda Claudia (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
This study discusses the effectiveness of using Communicative Language Teaching in essay writing. The research method used experimental quantitative method. The design of research was a quasi-experimental research using a one group pretest-posttest model. Written test was an instrument that was applied in research to obtain research data. In analyzing the data, the steps taken consisted of 1) counting mean of pretest and posttest, 2) counting standard deviation of the pretest and posttest, 3) counting normality of the pretest and posttest, 4) counting the homogeneity of the pretest and posttest, and 5) testing the hypothesis. The result of the study shown that the using of Communicative Language Teaching was effective to be implemented in essay writing. This is proved by the value of tcount > ttable = 4.30> 1.70329. That means Ha is accepted and Ho is rejected. In this case, all students are more enjoyable in learning essay writing in class and they are motivated to improve their skill especially in writing essay